A tailored distractor-assisted percutaneous minimally invasive treatment for Sanders II and III calcaneus fractures: a consecutive cohort study with medium-term results - Liao, Xiong; Deng, Jianliang; Liu, Wei; You, Di (Frontiers in Surgery, 2025)
BackgroundThe treatment strategy of displaced intra-articular calcaneal fractures (DIACFs) remains challenging. While the operation techniques vary widely, the efforts is now on the optimization of surgical techniques to better DIACFs management. This study aimed to introduce a tailored distractor-assisted percutaneous minimally invasive surgery (MIS) and reported its medium-term outcomes in patients with Sanders II and III calcaneus fractures.Methods63 cases (63 feet) of DIACFs, subjected to a tailored distractor-assisted MIS in our orthopedic department were retrospectively analyzed. The medical records and radiological measurements were retrieved for efficiency evaluation. At the last follow-up, the American Orthopaedic Foot & Ankle Society (AOFAS) ankle-hind foot score and Visual Analog Scale (VAS) score were used to evaluate the functional rehabilitation. Postoperative complications were also recorded.ResultsAll feet (39 Sanders type II fractures and 24 Sanders type III) successfully achieved fracture reduction with the interval between injury to operation average 1.3 days, the duration of surgery average 40.1 min, and the hospital stay average 4.9 days. Radiographic measurements revealed significant differences between pre-operation and post-operation in calcaneal height and width, so as to Bohler's angle and Gissane angle (p < 0.05, respectively). Anatomical or near-anatomical realignment of the posterior subtalar articular surfaces were achieved in all cases. At the last follow-up, the AOFAS and the VAS score was average 81.4 and 1.3 points, both significantly improved from that of pre-operation (p < 0.05, respectively). Four feet (6.3%) encountered postoperative complications.ConclusionApplication of the tailored calcaneal distractor in MIS for Sanders type II and III calcaneal fractures has demonstrated advantages in effectively manipulating fracture reduction and yielding favorable clinical outcomes. Further cohort study is required to clarify its clinical significance vs. other techniques.